Spatial navigation—a unique window into physiological and pathological aging - Gazova, Ivana; Vlcek, Kamil; Laczo, Jan; Nedelska, Zuzana; Hyncicova, Eva; Mokrisova, Ivana; Sheardova, Katerina; Hort, Jakub (Frontiers in Aging Neuroscience, 2012)
Spatial navigation is a skill of determining and maintaining a trajectory from one place to another. Mild progressive decline of spatial navigation develops gradually during the course of physiological ageing. Nevertheless, severe spatial navigation deficit can be the first sign of incipient Alzheimer’s disease (AD), occurring in the stage of mild cognitive impairment (MCI), preceding the development of a full blown dementia. Patients with amnestic MCI, especially those with the hippocampal type of amnestic syndrome, are at very high risk of AD. These patients present with the same pattern of spatial navigation impairment as do the patients with mild AD. Spatial navigation testing of elderly as well as computer tests developed for routine clinical use thus represent a possibility for further investigation of this cognitive domain, but most of all, an opportunity for making early diagnosis of AD.